RT500/RT800 Sandwich Composite Laminate with COREMAT Subjected to Bending Tests. (2015) - Galfi, Botond-Pal; Ionescu, Raluca Dora; Munteanu, Renata; Secara, Eugenia
Abstract: In this paper, the most important mechanical features determined in three-point bend tests of a sandwich composite laminate with glass-fibre reinforced dissimilar skins and embedded nonwoven polyester mat as core are presented. The nonwoven polyester mat known as COREMAT increases the overall stiffness of a composite laminate by the increase of the entire thickness of the laminate. The skins are dissimilar, the upper one has a polyester reinforced RT500 and RT800 glass roving fabric and the lower one is a gelcoat layer reinforced with a chopped strand mat CSM450. Following main mechanical properties have been determined: stiffness, Young's modulus of bending, flexural rigidity, load/stress/strain at maximum load, load/stress/strain at maximum extension, load/stress/strain at minimum load, load/stress/strain at minimum extension, work to maximum load/extension, work to minimum load/extension and load/stress at break.